THE ROLE OF EMOTIONALLY INTELLIGENT AI IN SUPPORTING PRE-SERVICE TEACHERS - Nizomov Feruz; Shaydullayeva Dilrabo (Bright Mind Publishing, 2025)
This article examines the role of emotionally intelligent artificial intelligence (EI-AI) in pre-service teacher education. Teaching requires not only subject expertise but also emotional competence, self-awareness, and resilience. EI-AI systems can support pre-service teachers by providing adaptive feedback, monitoring emotional states, and creating safe spaces for reflection and growth. The study highlights key benefits such as personalized guidance, emotional support, and real-time feedback, while addressing ethical concerns including privacy, bias, and over-reliance on technology. The paper concludes that integrating EI-AI with human mentorship offers a balanced and effective approach to enhancing teacher preparation in Uzbekistan’s digital education context.
Keywords: Emotionally intelligent AI; pre-service teachers; emotional intelligence; teacher education; reflective practice; ethics in AI; digital pedagogy.